2020
DOI: 10.1111/jfpp.14963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonication pretreatment on physicochemical, surface, thermal, and functional properties of fibro‐proteic extracts from male date palm flowers

Abstract: This study aims to investigate the effect of the application of an ultrasound pretreatment on physicochemical, surface, thermal, and functional properties of two extracts from male date palm flowers. The obtained extracts were compared based on their structural and functional properties. It was proved that the application of sonication pretreatment has modified significantly (p < .05) the extract's characteristics. The protein yield, the essential amino acid content and the protein solubility were improved (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(70 reference statements)
2
3
0
Order By: Relevance
“…However, an increase in particle size was observed depending on the increase in sonication process time. These findings were in agreement with studies conducted by Ding, Tian, Wang, Deng, Mao, and Sang [33] and Karra et al [51]. Zou, Shi, Chen, Xu, Jiang, Xu, and Wang [50] also reported that the protein molecular structure breakdown, particle size reduction, protein aggregate dispersion, and creation of looser layer structures after lyophilization are all potential effects of ultrasound treatment.…”
Section: Protein Solubilitysupporting
confidence: 92%
See 2 more Smart Citations
“…However, an increase in particle size was observed depending on the increase in sonication process time. These findings were in agreement with studies conducted by Ding, Tian, Wang, Deng, Mao, and Sang [33] and Karra et al [51]. Zou, Shi, Chen, Xu, Jiang, Xu, and Wang [50] also reported that the protein molecular structure breakdown, particle size reduction, protein aggregate dispersion, and creation of looser layer structures after lyophilization are all potential effects of ultrasound treatment.…”
Section: Protein Solubilitysupporting
confidence: 92%
“…On the other hand, ultrasonic power higher than 500 W or long sonication time cause an increase in particle size [33,51]. It was observed that increasing the sonication time from 2 to 4 min led to a relative increase in particle size, and this increment was significant (p < 0.05) when the sonication time was increased to 6 min.…”
Section: Protein Solubilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Sonication and irradiation caused microstructural changes at the molecular level. These changes may be attributed to fragmentation, cross-linking and aggregation, as previously observed by other authors [61,[72][73][74][75].…”
Section: Treatment Effect (Ratiosupporting
confidence: 76%
“…US + PEF treatment, particularly at higher intensities, might activate proteolytic enzymes within muscle cells, resulting in increased protein breakdown and the release of constituent amino acids. For instance, Karra et al [58] and Fadimu et al [22] found that ultrasound pre-treatment enhanced the extraction of amino acids, particularly hydrophobic amino acids, indicating that ultrasound can affect the breakdown of proteins into amino acids and facilitate the release of amino acids from biological matrices.…”
Section: Resultsmentioning
confidence: 99%